Penguatan Kemampuan Manajerial Kelompok Tani Melalui Pelatihan Laporan Keuangan Usahatani di Sungai Beduk Kota Batam - Sri Ariani Safitri (Jurnal Pengabdian Barelang, 2021)
The Sei Beduk Farmers Group of Batam City has not conducted simple farm records. Community service activities aim to improve farmers' knowledge and skills in conducting simple financial reports. The method used the form of training with material in the form of examples of making financial reports. Participants' participation was considered very good as indicated by the activeness of the farmers in conducting discussions. Training activities show that farmers have started to understand simple financial reports and will apply them in farming activities